Tramp iron in chopped hay: Electronic device detects and removes bits of iron from chopped hay pneumatically conveyed at high speeds - Dobie, John B.; Jacob, Frederic C.; Kleist, Leroy C. (California Agriculture, 1953)
An experimental tramp-iron remover successfully ejected 99% of the wire and nails in chopped hay during tests with pneumatic conveyors at hay and air speeds up to 6,000' per minute.